EVALUASI DAMPAK KEBIJAKAN PEMBERDAYAAN PEREMPUAN PESISIR KECAMATAN TAHUNA BARAT KABUPATEN KEPULAUAN SANGIHE - MAKISAKE, NOVITSON; Rompas, Sonny; Londa, Very (Sam Ratulangi University, 2015)
Abstract: The majority of women are still confined within the limitations or poverty , whether caused bystructural poverty , cultural and natural . If when viewed from the standpoint of structural poverty , thepoverty caused by discriminatory policies or regulations , it is the reality of women's groups to bemarginalized . This is evident from the persistence of the treatment was discriminatory , either in theprovision of access to education , economic access ( including access to the world of work , salary , accessto the distribution of economic independence ) , as well as access in the political field .The research method is basically determined by the research question . Based on the researchquestions , the research was conducted using qualitative and quantitative research methods . Qualitativeresearch methods focus to see the pattern of the empowerment of women coastal conducted by theDistrict Government of Sangihe while quantitative method for measuring the success of the results(intermediate outcomes) women's empowerment programs coast at the same time to see the impact (finaloutcomes) change perceived by women after getting the programs carried out by the TechnicalImplementation Unit of PNPM Mandiri , especially in improving the living standards of families ofwomen who benefit from the program.Results of analysis of data obtained from the results of Questionnaire ( questionnaire ) to 60respondents women / mothers of households spread across three sample villages in the subdistrict of WestTahuna Regency of Sangihe Islands . Results of the study are presented in three parts: the first part ,presenting the results of research concerning the description of women's empowerment factors , whichinclude : ( 1 ) educational factors ; and ( 2 ) factors training / skills ; The second part , presenting theresults of research on the condition of the family living standards ; while the third section presents theresults of statistical analysis and discussion of the influence of factors of women's empowerment on thecondition of the living standards of families .Keywords : Coastal Women's Empowerment Policy .